RUNX3 in Stem Cell and Cancer Biology - Linda Shyue Huey Chuang; Junichi Matsuo; Daisuke Douchi; Nur Astiana Bte Mawan; Yoshiaki Ito (Cells, 2023)
The runt-related transcription factors (RUNX) play prominent roles in cell cycle progression, differentiation, apoptosis, immunity and epithelial–mesenchymal transition. There are three members in the mammalian RUNX family, each with distinct tissue expression profiles. RUNX genes play unique and redundant roles during development and adult tissue homeostasis. The ability of RUNX proteins to influence signaling pathways, such as Wnt, TGFβ and Hippo-YAP, suggests that they integrate signals from the environment to dictate cell fate decisions. All RUNX genes hold master regulator roles, albeit in different tissues, and all have been implicated in cancer. Paradoxically, RUNX genes exert tumor suppressive and oncogenic functions, depending on tumor type and stage. Unlike RUNX1 and 2, the role of RUNX3 in stem cells is poorly understood. A recent study using cancer-derived RUNX3 mutation R122C revealed a gatekeeper role for RUNX3 in gastric epithelial stem cell homeostasis. The corpora of RUNX3R122C/R122C mice showed a dramatic increase in proliferating stem cells as well as inhibition of differentiation. Tellingly, RUNX3R122C/R122C mice also exhibited a precancerous phenotype. This review focuses on the impact of RUNX3 dysregulation on (1) stem cell fate and (2) the molecular mechanisms underpinning early carcinogenesis.